The Right to Strike under the labour relations Act 66 of 1995 (LRA) and possible factors for consideration that would promote the objectives of the LRA - Subramanien, Darren C; Joseph, Judell L (PER/PELJ, 2019)
The Labour Relations Act 66 of 1995 (hereafter the LRA) was promulgated to redress the injustices and inequality within labour relations. It seeks to do so through four objectives which give effect to the LRA's purposes of transformation within the labour relations framework. One of these objectives is to promote orderly collective bargaining. It is envisaged that if parties engage in collective bargaining, then disputes should be resolved speedily and amicably without having employees resort to strikes and employers to lock-outs. This in turn would ensure that production within the workplace continues without interruption. Thus, the workdays lost would be decreased and productivity would be increased. One of the main features of the LRA is the endorsement and regulation of strike action. Employers have always possessed greater authority than employees due to their managerial prerogative, thus strike action is viewed as a necessary way of levelling the playing field between employers and employees in the collective bargaining framework. Strike action is regarded as forming part of the collective bargaining framework. It has been acknowledged that without the threat of strike action, collective bargaining would be futile. However, strike action in South Africa has been increasingly alarming over recent years. This is primarily due to the manner in which employees are asserting their demands. There has been an undeniable increase in the intensity of violence, intimidation, harassment, destruction to property and civil unrest evident in strikes. Even more disturbing is that these strikes have not been contained within the employment relationship; instead, the ramifications of disorderly strikers have caused severe consequences for innocent members of society and the country as a whole. This article highlights the violent context in which strikes take place and the necessity of limiting potential violence. In doing so, this article seeks to consider the viewpoints of two judgments, Equity Aviation Services (Pty) Ltd v SA Transport & Allied Workers Union 2011 32 ILJ 2894 (SCA) and SA Transport & Allied Workers Union v Moloto 2012 33 ILJ 2549 (CC), which have addressed the issue of whether non-unionised members are required to provide separate notices of their intention to strike. It is argued that a strict interpretation of section 64(1)(b) of the LRA is required, in the light of the chaotic and violent strike action that has taken place over the years, as that would have the effect of creating greater certainty and predictability in the event of a strike. Thus, an expectation of order would be instilled which in turn would fulfil one of the objectives of the LRA, which is to promote orderly collective bargaining.
Keywords: Labour Relations Act 66 of 1995; collective bargaining; strike action; violence; intimidation; Equity Aviation case; Moloto case